The Effects of Breeder Age and Hatching Period on Fattening Performance and Carcass Characteristics in Geese - EROGLU, Mehmet; ERISIR, Zeki (Emirates Journal of Food and Agriculture, 2022)
This study was carried out to determine the effects of breeding age and hatching period on fattening performance and slaughter characteristics in geese. For this purpose, were fattened 270 geese obtained from three different ages of geese breeder (one, two, three years old), and 54 of them were slaughtered at the age of 16 weeks to evaluate their carcass characteristics The values of 81.06, 94.15, and 93.37 g for hatching weights, 5275.27, 5590.25, and 5604.90 g for body weights at the 16th week, 24.57, 25.53, and 25.75 kg for total feed consumption and 3592.00, 3814.98, and 3850.6 g for warm carcass weight were determined in the evaluation of carcass characteristics of geese from obtained one, two and three years old breeder geese, respectively. The results of the present study suggested that breeder age had statistically significant effects on hatching weight (P<0.001), body weight (P<0.05), total feed consumption (P<0.01), warm and cold carcass weights (P<0.01). The hatching weights of 92.81 and 86.24 g, total feed consumption values of 24.91 and 25.66 kg, feed conversion ratios of 4.57 and 4.80 were calculated in the first and second periods. The difference in the hatching period was detected to have statistically significant effects on hatching weights (P<0.001), feed consumption (P<0.05), feed conversion ratio (P<0.01), and abdominal fat weights (P<0.001). In addition, it was suggested that seasonal variations could create differences in themselves depending on the stages of the growth and development process.